2020
DOI: 10.1590/1678-6971/eramr200199
|View full text |Cite
|
Sign up to set email alerts
|

Sales Capability and Performance: Role of Market Orientation, Personal and Management Capabilities

Abstract: Purpose: This article aims to explain the relationships between sales capabilities, which are split into personal selling and sales force management, both from the manager’s point of view, and financial/customer performance in market-oriented firms. Originality/value: This research is the first that explores in-depth sales capabilities and demonstrated that these capabilities need a previous strategic orientation. It checks different types of performance that can be the result of these two capabilities. We ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 40 publications
0
8
0
2
Order By: Relevance
“…Among other things, this sales capability contributes significantly to performance generation and improvement. It is the most faithful and appropriate capability for the organization's goal at the organizational level, and it is the capability best suited for individual duties or responsibilities at the individual level [24]. Previous research has identified a number of specific elements that comprise a salesperson's sales capability.…”
Section: Salesperson's Individual Sales Capabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Among other things, this sales capability contributes significantly to performance generation and improvement. It is the most faithful and appropriate capability for the organization's goal at the organizational level, and it is the capability best suited for individual duties or responsibilities at the individual level [24]. Previous research has identified a number of specific elements that comprise a salesperson's sales capability.…”
Section: Salesperson's Individual Sales Capabilitymentioning
confidence: 99%
“…According to Spencer and Spencer [22], capability is an indicator of the behavior and mentality that employees must consistently exhibit to function in a variety of job-related scenarios. It is defined as a set of technical attitudes or indicators that can be improved and quantified through continuous development and performance in critical areas, with capability focusing on the specific behavioral traits of individuals in the work process [24]. Specific activities undertaken while performing work, as well as the professional knowledge, talents, personality, and attitude of the individual, are regarded as necessary to foster good capabilities [34].…”
Section: Individual Sales Capability Of Door-to-door Salesperson and ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The main focus of sales management is to meet the short-term needs of consumers, within the framework of the production approach that prevails in periods when competition is limited and demand is more than supply (Rodrigues and Martins, 2020). In this understanding, where management efforts are directed towards large-scale production of standardized products and production efficiency, the basic philosophy is that affordable products will be able to be sold to large consumer masses, provided that they are of reasonable quality (Schrock et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing sales and access to the website is the first strategy that an e-commerce seeks when working with more active marketing strategies, as with online discount coupons (Rodrigues & Martins, 2020). By offering a discount coupon for your customers, the company stands out from its competitors and awakens an interest in purchasing their products in the consumer, who can identify immediate savings opportunity for financial discount.…”
Section: Introductionmentioning
confidence: 99%